Quasi-persistent currents in the high field phase of α-(BEDT-TTF)2TlHg(SCN)4: evidence for quantum Hall effect - Gee, P; Harrison, N; Kartsovnik, M; Polisski, A; Singleton, J; Blundell, S; Herlach, F (Elsevier, 1997)
Magnetisation measurements performed on the charge-transfer salt α-(BEDT-TTF)2TlHg(SCN)4 in pulsed magnetic fields reveal the existence of eddy current 'resonances' in the high field state, indicating the presence of deep minima in the transverse magnetoresistivity (or ideal conducting phases). Their behavior can be explained qualitatively in terms of enhanced conductivity due to the quantum Hall effect, which becomes possible even when quasi-one-dimensional carriers are present.